A Study on the Factors that Affect the Patients' Treatment Seeking Behavior in Multibranch Dental Clinic in Selected Cities of Metro Manila during the COVID-19 Pandemic/Lexine Nicole G. Martires. - Martires, Lexine Nicole G.
INTRODUCTION: This study explores the factors that affect the patients' treatment seeking behavior in a multibranch dental clinic across selected cities of Metro Manila during the COVID-19 pandemic. The lack of data available regarding the effects of the pandemic to Filipinos’ dental treatment seeking behavior is concerning, especially given the fact that similar data is available internationally. This study aimed to gather the necessary data needed to describe the factors that affected the patients’ treatment seeking behavior in Metro Manila during the COVID-19 Pandemic. It examined both preexisting factors and newly introduced challenges influencing patients' treatment seeking behavior regarding dental care during the pandemic, drawing from sociodemographic data, vaccination statuses, anxiety levels, and patient concerns. The research highlights key insights into the evolving landscape of dental healthcare in the Philippines during the pandemic.